Tuberculosis mortality in Spain, 2008-2021 (Boletín Epidemiológico Semanal, 2024)
Introduction: Tuberculosis (TB) has a high burden of morbidity and mortality, being the leading cause of mortality due to an infectious agent in the world, only recently surpassed by COVID-19. The aim of this study was to analyse the spatio-temporal evolution of TB mortality in Spain between 2008-2021.Method: Descriptive epidemiological analysis of TB deaths registered in the National Institute of Statistics (INE) during 2008-2021. The variables analysed were sex, age, province and year of death. A descriptive analysis of the main variables and a temporal-spatial analysis of mortality rates (MR) and standardised mortality ratios (SMR) were performed.Results: Between 2008 and 2021, 3,876 TB deaths were reported, with an average MR of 0.6 per 100,000 population. More than 60% of deaths occurred in people over 75 years old. There was a decreasing trend in the MR with an average annual percentage change (APC) of -5.2%. A higher number of deaths was observed in men (64.1%), as well as a greater decrease in their MR (PACMA -5.5% vs. -4.5% in women). All provinces decreased their MR except Palencia, Cantabria and Huesca. SMRs were distributed differently according to sex, with an excess of observed deaths over expected deaths in men.Conclusions: The TB MR in Spain has followed a downward trend since 2008, although with an unequal pattern and evolution by sex and province. Further studies are needed to explain the differences observed.
Keywords: Tuberculosis; Mortality, Spain